Determinants of non-completion of sleep apnea testing during pregnancy - Antony, Kathleen M.; Rice, Alexandra Lauren; Bajaj, Sakshi; Wiedmer, Abigail M.; Jacobson, Natalie; Nick, Julia; Eichmann, Allison; Stanic, Aleksandar K.; Bazalakova, Mihaela H. (Frontiers in Sleep, 2023)
Study objectives Completion of testing during pregnancy for those who screen positive for obstructive sleep apnea (OSA) is imperative for the diagnosis and treatment of OSA, as the latter may reduce the risk of developing hypertensive disorders of pregnancy. To identify potential barriers, we assessed predictors of non-completion of sleep apnea testing by people identified to be at high risk of OSA by screening during pregnancy. We hypothesized that non-completion of sleep apnea testing would be predicted by insurance status and obstetric factors, such as gestational age at time of testing. Methods We performed a retrospective analysis of the first 500 people in our sleep pregnancy database which includes both pregnant and preconception patients who screened positive for OSA; those screened preconception were excluded. Multivariable Poisson regression was used to determine which factors were independently associated with non-completion. Results Of 445 referred, 214 (48.1%) completed sleep apnea testing. Factors associated with non-completion of testing on univariate analysis included referral in the third trimester, higher parity, one or more living children, history of preterm birth, history of preeclampsia, type 2 diabetes mellitus, non-partnered status, race, and payor. Symptoms of loud snoring or witnessed apneas were associated with increased incidence of sleep apnea testing completion. Multivariable Poisson regression demonstrated that having public insurance predicted non-completion of sleep apnea testing during pregnancy. Conclusion In this small study, public insurance was an independent predictor of non-completion of sleep apnea testing during pregnancy. These findings aid efforts to improve patient completion of sleep apnea testing during pregnancy.